Strategi Adaptasi Orang Laut Masa Pandemi Covid-19 di Kabupaten Lingga, Kepulauan Riau - Arman, Dedi; Swastiwi, Anastasia Wiwik (Warisan: Journal of History and Cultural Heritage, 2023)
This paper examines the adaptation strategies used by Orang Laut in Lingga Regency, Riau Archipelago Province during the Covid 19 pandemic. The research uses historical research methods. From research, it is known, data from the the Kajang Lingga Foundation, that at the peak of the 2020-2021 pandemic, no Orang Laut were found to have contracted Covid 19. Orang Laut had adaptation strategies during the Covid 19 pandemic. Social restrictions were very effective because the Orang Laut villages were separated from the community. other. The sea people do not understand the disease outbreak that is happening but what they do know is that they are not allowed to leave their village. The nature that is still maintained and the diversity of food, make marine people more prepared to face a pandemic in the long term. Staple foods in the form of sago and fish help them remain independent during the pandemic. In medicine, the Orang Laut rely on traditional medicine to cure certain diseases. Medicines come from plants and animals which during treatment are usually accompanied by a spell by a bomoh (dukun). The ability to recognize plant and animal species, as well as the spells used, is passed down from generation to generation through oral speech from parents